2000
DOI: 10.1046/j.1439-0442.2000.00274.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Infectious Keratoconjunctivitis in Cattle in South‐east Ethiopia

Abstract: The aim of the study was to determine the prevalence of infectious keratoconjunctivitis on cross-breed dairy farms and to evaluate factors that influence its distribution. A total of 11 dairy farms and one cattle cross-breeding farm in different parts of Arsi region, south-east Ethiopia were clinically and bacteriologically investigated from February 1989 to December 1990. Out of 5221 local zebu and cross-breed dairy animals, 110 were found to have different degrees of infectious bovine keratoconjunctivitis. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 4 publications
3
6
0
Order By: Relevance
“…Similar findings found in this study which indicated that younger and older animals were more susceptible to the disease than adults. In this study, the occurrence of disease was more in the exotic breed that was in agreement with the report of Takele and Zerihun [10]. Which also stated that the exotic breed made them susceptible to infectious keratoconjunctivitis compared to other breeds.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar findings found in this study which indicated that younger and older animals were more susceptible to the disease than adults. In this study, the occurrence of disease was more in the exotic breed that was in agreement with the report of Takele and Zerihun [10]. Which also stated that the exotic breed made them susceptible to infectious keratoconjunctivitis compared to other breeds.…”
Section: Discussionsupporting
confidence: 92%
“…Stated the occurrence of disease was higher in intensive rearing system due to a spread of infection from one to another animal rapidly in Putra Malaysia that was not agreed with our findings which were more in backyard rearing system. The higher number of IKC cases found in our study in backyard rearing system could be due to a majority of goat patients in TVH from smallholders, infection from other animal and trauma to the eye during grazing [10]. Reported that clinical keratoconjunctivitis was highest in young and old animals which were probably because young animals lack immunity owing to the absence of previous exposure and in the old animal due to weak immunity.…”
Section: Discussionmentioning
confidence: 50%
“…In current study bacteriological examination of swabs from diseased animals yielded several species of bacteria in which Moraxella spp., corynbacterium spp., Listeria spp. and E. coli were the most common isolates, similar findings were also reported by (10,20,21,22). Seham and Mohammed (23) isolated Staphylococcus and E. coli from infected calves and showed that they were the predominant organisms responsible for infectious keratoconjunctivitis, they further reported that Staphylococcus occurred more frequently and severely than mildly affected eyes, whereas (24) isolated more than 14 species of both gram positive and negative microorganism from bovine eyes exhibited clinical sings of keratoconjunctivitis and they considered that M. bovis, Corynebacterium bovis, Niesseria catarrhalis and Chlamydiae spp.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, 36 Moraxella bovis strains were isolated from 46 samples obtained from affected eyes of cattle with symptoms of IBK. Varied susceptibility between various breeds of cattle and ages of animals has been reported 22,23 . In the present study, the findings indicated that younger animals were more susceptible to the disease than adults.…”
Section: Discussionsupporting
confidence: 53%